Ethical Dilemmas of Migration Moral Challenges for Policymakers - Garcia-Zamor, Jean-Claude (Public Administration, Governance and Globalization ;, 2018)
This book discusses the ethical dilemmas of migration in the era of globalization. Centered on the recent influx of large numbers of migrants and refugees to the United States and Europe and viewed through the lens of the 2016 World Humanitarian Summit and the United Nations Summit on Refugees and Migrants, this book focuses on the problems posed by globalized migration and analyzes proposed responses. Using prominent ethical theories and moral principles, such as Utilitarianism, duty, justice, and integrity, the book proposes a framework for analyzing decision-making by migrants and policymakers and formulating equitable policies to address the migration crisis. Drawing attention to the ethical dilemmas that migrants and policymakers experience, this book fills a gap in the literature and enriches it, adding to the economic, political, and human rights issues that are traditionally part of the migration discussion. Appropriate for students and scholars of ethics, policy, and political science, this book is also meant to be of use to practitioners and decision-makers faced with similar decisions. .